Nutritional status of under-5 Rohingya Children admitted for Diarrheal Diseases at Primary Health Centers in Cox’s Bazar District of Bangladesh (Bangladesh Journal of Infectious Diseases, 2023)
Background: One of the leading causes of mortality and morbidity in under-5 children is Diarrhea. Malnutrition, in association with the diarrheal disease, affect children negatively. On 2018, Bangladesh saw massive influx Rohingya people with almost 29% under-5 children.Objective: The purpose of the present study was to determine the prevalence of malnutrition among children admitted with acute diarrheal diseases at the Primary health Centers at Cox’s Bazar.Methodology: This cross-sectional study was conducted among the diarrhea affected under-5 Rohingya children who reported to primary health centers at cox’s bazar. The study was conducted from January to December 2018. Primary caregiver of 276 respondents were interviewed, their hospital records were reviewed. Data were collected by face-toface interview using a semi-structured questionnaire.Results: The majority (60.1%) of the participants were male. Only 2.9% of the participants reported passing of macroscopic blood in stool. Oral Rehydration Solution (ORS) was not taken by most of the participants (50.7%), prior to visit to the hospital. The mean (±SD) age was 18.54 (±12.44) months. Among the participants, 14.1% had severe underweight (